2014
DOI: 10.1590/0104-1169.3389.2449
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiovascular risk factors with the different presentations of acute coronary syndrome

Abstract: OBJECTIVE: to identify the relationship between different presentations of acute coronary syndrome and cardiovascular risk factors among hospitalized individuals. METHOD: cross-sectional study performed in a teaching hospital in São Paulo, in the State of São Paulo (SP). Socio-demographic, clinical and anthropometric data of 150 individuals hospitalized due to acute coronary syndrome were collected through interviews and review of clinical charts. Association between these data and the presentation of the synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
(26 reference statements)
5
7
0
17
Order By: Relevance
“…The sociodemographic profile of participants of this study, the risk factors presented, and their comorbidities are similar to those observed in the literature. (16,17) The state anxiety level was significantly higher prior to catheterization than after. This was expected because the state anxiety level increases in threatening situations and tends to decrease when the threat is controlled or no longer exits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The sociodemographic profile of participants of this study, the risk factors presented, and their comorbidities are similar to those observed in the literature. (16,17) The state anxiety level was significantly higher prior to catheterization than after. This was expected because the state anxiety level increases in threatening situations and tends to decrease when the threat is controlled or no longer exits.…”
Section: Discussionmentioning
confidence: 97%
“…Anxiety has been associated with the onset and progression of cardiovascular diseases, as well as with adverse cardiovascular outcomes, including mortality. (16) This study analyzed the relationship of anxiety scores assessed by the STAI-state and STAI-trait with short-term outcomes in patients with ACS undergoing unplanned catheterization. The results of this study may contribute to improve the understanding of the influence of this phenomenon mediated by intervening factors (age, sex, educational level, cardiovascular risk factors, comorbidities and depression) in these patients' health.…”
Section: Discussionmentioning
confidence: 99%
“…En este trabajo se encontró que el factor de riesgo coronario más frecuente en pacientes con IAM fue la HTA, mayor que en el estudio realizado por Rodríguez Navarro y col. en un hospital de Cuba y por (11,12) Brunori y col en Brasil . Esta diferencia podría deberse a que los pacientes estudiados poseen un rango etario en su mayoría por encima de los 60 años.…”
Section: Discussionunclassified
“…Con respecto a los otros factores de riesgo coronarios descritos, llama la atención la alta frecuencia de sedentarismo y de consumo de tabaco, similar a la reportada por otros estudios (17,18) realizados en Colombia y Cuba . También en otras regiones del mundo encontraron que frecuencia (12,14,(19)(20)(21)(22) alta de sedentarismo y de consumo de tabaco como factores de riesgo coronario . En relación a (23) la dislipidemia, c-HDL cumple un rol importante como predictor de enfermedad cardiovascular .…”
Section: Discussionunclassified
See 1 more Smart Citation